2017
DOI: 10.1097/eja.0000000000000647
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dexamethasone on early cognitive decline after cardiac surgery

Abstract: Clinicaltrials.gov identifier: NCT02767713.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(143 citation statements)
references
References 31 publications
5
131
0
7
Order By: Relevance
“…Two studies reported the duration of hospitalization (measured in days) [22,23]. Our meta-analysis showed that the use of dexamethasone reduced the length of hospital stay (WMD -0.57 d; 95% CI [-1.08, -0.07], P =0.03, I2 = 0%, Figure 6), but the difference was so small that it did not has a clinical significance.…”
Section: Secondary Outcomesmentioning
confidence: 76%
See 4 more Smart Citations
“…Two studies reported the duration of hospitalization (measured in days) [22,23]. Our meta-analysis showed that the use of dexamethasone reduced the length of hospital stay (WMD -0.57 d; 95% CI [-1.08, -0.07], P =0.03, I2 = 0%, Figure 6), but the difference was so small that it did not has a clinical significance.…”
Section: Secondary Outcomesmentioning
confidence: 76%
“…Table 1 shows the characteristics of the included studies. Four of the included studies involved cardiac surgery [22][23][24][25], while the remaining one involved microvascular decompression surgery [26].…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations